Pengaruh citra merek, kemasan dan iklan terhadap perilaku pembelian konsumen pada produk minuman isotonik Mizone di Surabaya - Leonita Rachmadini; Ronny Ronny (Journal of Business & Banking, 2015)
Brand image has an effect on buying behavior. Consumers, who have a positive image of the brand, tend to choose the brand when buying. In addition to brand image, the packaging and advertisement can slo affect buying behavior. Innovative packaging can provide benefits to the company exceeds the competitors and to encourage sales, while a badly designed packaging can lead to consumers switching to a competitor's product and the company lost sales, and advertisement is behaving as a driving force for any business as it's an effective source to convey marketing message and stay in consum-er's mind. The purpose of this study is to examine the influence of brand image, pack-aging and advertisement on consumer buying behavior of Mizone isotonic drink in Surabaya. Questionnaire is used as an instrument to get the response of the respon-dent. Questionnaires were spread to one hundred people who buying the Mizone iso-tonic drink in Surabaya. Multiple Regression Analysis is used to examine the effect of the independent variables on dependent variable. The findings of this study shows brand image and packaging have positive significant effect on consumer buying beha-vior, but not to advertisement. The impilcation of this research, the company should improve the quality of Mizone isotonic drink and replace Mizone packaging materials with environmentally friendly packaging materials.